High‐Performance Micro‐Radioisotope Thermoelectric Generator with Large‐Scale Integration of Multilayer Annular Arrays through Screen Printing and Stacking Coupling. Issue 5 (24th March 2021) - Yuan, Zicheng; Tang, Xiaobin; Cabot, Andreu; Xu, Zhiheng; Liu, Kai; Wang, Hongyu; Liu, Yunpeng; Bian, Minxing; Meng, Caifeng; Jiang, Tongxin
Abstract : Small distributed scientific monitoring equipment is an advanced concept in deep space exploration that requires a special power system. A micro‐radioisotope thermoelectric (TE) generator has the advantages of being of small volume, lightweight, and having a long life, which is regarded as the first choice. An annular radial TE conversion structure integrating 30 TE legs in 8.8 cm 3 is designed, and a satisfactory temperature difference of 188.4 K is demonstrated. The p‐type Sb2 Te3 and n‐type Bi2 Te2.7 Se0.3 TE thick films are prepared by screen printing, and Seebeck coefficients are 142.4 and −179.8 μV K −2, respectively. By serial–parallel stacking, modular single‐layer devices are effectively integrated on a large scale. The 900 TE legs are integrated into 15.86 cm 3, which can provide a high voltage output of up to 13.2 V. When an electric heating source that simulates 3 PuO2 is loaded, an open circuit voltage of 3.84 V and a maximum power of 1.26 mW can be obtained. As a demonstration, a prototype to drive a wireless sensor network is used. In the future, this kind of independent power source is expected to become a help for small autonomous and distributed scientific instruments. Abstract : This work reports the integration of many modular devices through screen printing and stacking. The expanded annular power generation module has an excellent voltage application range with the source. The micro‐radioisotope thermoelectric generator (RTG) prototype device drives two independent wireless sensor network nodes, which is expected to provide a new solution for space micro‐energy.